Asian Resources for a Population Library Information Network : Report of a Working Meeting (Bangkok, Thailand, September 13-15, 1973). Asian Population Studies Series No. 19/A - United Nations Economic and Social Commission for Asia and the Pacific, Bangkok (Thailand).; United Nations Economic and Social Commission for Asia and the Pacific, Bangkok (Thailand). ([Washington : Distributed by ERIC Clearinghouse, 1973)
A working meeting in Bangkok, Thailand, September 13-15, 1973, was called to consider three main topics: (1) the current status of exchange of information on population and family planning; (2) the feasibility of establishing national and regional networks for collection and dissemination of information on population and family planning; and (3) the operational aspect of such networks. This report summarizes the proceedings of panel discussions and work groups and lists the recommendations posited by the conference participants. (EMH)
Sponsoring Agency: North Carolina Univ., Chapel Hill. Carolina Population Center.
Sponsoring Agency: Agency for International Development (Dept. of State), Washington, DC.
Microfiche.
Keywords: Conference Reports; Developing Nations; Family Planning; Feasibility Studies; Information Centers; Information Needs; Information Networks; Population Education; Special Libraries; Asia; Collected Works, Proceedings